Using Total Physical Response (TPR) Method on Young Learners English Language Teaching - Cicih Nuraeni (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
The purpose of this study was to describe the use of Total Physical Response (TPR) method on young learners English Language Teaching (ELT) at Panti Asuhan Yauma. The method of the research is descriptive qualitative. In this research the researcher describes the activities carried out by teachers and students by using TPR method. The data resources are from teacher and students in Panti Asuhan Yauma Jakarta. The class consists of 30 students which their ages were around 5 to 11 years old. The data collected through observation in learning activities. The instruments were pre-test and post-test with 2 (two) criterion being assessed, namely vocabulary and comprehension. They were divided into 5 (five) elements such as accuracy of word, understanding each word, word choice, understanding the meaning, and speaking easily. The results showed that there was an improvement in vocabulary score about 27.40 and comprehension score about 28.77. The research finding first showed that when using the TPR method children enjoyed and were also very active in learning English. The researcher hopes that the study contributes to the activities of teaching and learning English, especially teaching English for young learners. It was proved by the score from pre-test and post-test.